Between silence, letters and ideas: university reading and writing, our experience - Ríos Nava, Bernabé; Olivo Estrada, J. Ramón; Montaño Torres, Carmelina (Rastros Rostros, 2021)
In recent years we have witnessed the lack of skills and abilities of our first-year university students in the composition of academic writings. I confronted this scenario through a proposal of educational intervention during the first semester in the Socioanthropology of Health class. The question is: how do we awaken interest and love for the composition of academics texts? This led me to: *) Build a theoretical foundation consisting of: 1) the constructivist approach from a cognitive perspective to highlight the development of thinking skills, meaningful learning and problem solving; 2) the sociocultural approach, to emphasize guided and cooperative learning and reciprocal teaching; 3) the macrostructural theory of Kinstch and Van Dijk to cultivate the ability to detect the keys of superstructural organization, and 4) the concept of academic literacy, to understand its dynamic, teaching and possible solutions (strategies) that favor the transition of students towards a full participation of the discursive disciplinary culture; *) Implement various curricular modifications. The approach motivated students to experience in body and soul the circumstances that a writer goes through; a reading and writing workshop was organized focused on the composition of two texts: autobiography and monograph. We conclude that the composition of the first text is adequate to initiate the students and accompaniment and group experiences are important components of the workshop.